Answer:

Step-by-step explanation:


Y² + 8y - 33 :
Break the expression into groups for formula ax²+ bx+c :
= (y²- 3y) + (11y - 33 )
Factor y from y² - 3y => y (y - 3)
Factor out 11 from 11 y - 33 => 11 (y - 3)
= y ( y- 3 ) + 11 ( y - 3 )
Factor out common term (y - 3 ) :
= ( y - 3 ) ( y + 11 )
hope this helps!
Area of the bases
<span>2π<span>r2</span>=2π∗784=1568π
</span>circumference of base
<span>2πr=56π
</span>extension of the height
<span>2πr∗h=56π∗48=2688π
</span>bases plus none base surface is total surface
<span><span>1568π+2688π=4256π</span></span>
The perpendicular would be -1/4